Nanoparticle Exposure and Workplace Measurements During Processes Related to 3D Printing of a Metal Object - Jensen, Alexander C. Ø.; Harboe, Henrik; Brostrøm, Anders; Jensen, Keld A.; Fonseca, Ana S. (Frontiers in Public Health, 2020)
Metal 3D printing has many potential uses within prototyping and manufacturing. Selective laser melting (SLM) is a process that uses metal powders in the micrometre range as printing material. The particle release from the entire SLM printing process is not well studied. While the 3D printing itself often occurs in a sealed chamber, activities related to the process can potentially release harmful metal particles to the indoor working environment through resuspension of the printing powder or via incident nanoparticles generated during printing. The objective of this study was to improve the understanding of particle exposure in work processes associated with 3D-printing and potential needs for interventions by a case study conducted in a 3D printing facility. In this setting, direct release and dispersion of particles throughout the workspace from processes related to metal 3D printing was investigated. The release from five activities were studied in detail. The activities included post-printing cleaning, object annealing, and preparation of new base substrate for the next printing was. Three of the five measured activities caused particles number concentrations in the working environment to increase above background levels which were found to be 8·102 cm-3. Concentrations during chamber emptying and the open powder removal system (PRS) cleaning processes increased to 104 and 5·103 cm-3, respectively, whereas grinding activity increased number concentrations to 2.5·105 cm-3. Size distributions showed that particles were mainly smaller than 200 nm. Respirable mass concentrations were 50.4 µg m-3, collected on filters. This was corroborated by respirable mass measured with a DustTrak of 58.4 µg m-3. Respirable mass concentrations were below the occupational exposure limits in Denmark for an 8h time-weighted average.